On the use of an high order perturbation method for numerical time integration in structural dynamics. - Claude, Bertille; Girault, Grégory; Leblé, Bruno; Cadou, Jean-Marc (Comptes Rendus. Mécanique)
This paper concerns numerical simulations of time-dependent problems in computational solid mechanics. A perturbation method, with the time as perturbation parameter, is proposed to solve two classical problems: an elastic bar excited by an end force and the dynamic buckling of a cylindrical panel. Specific quadratic recast of the equations is proposed to solve the nonlinear problems. Numerical results show that asymptotic time expansions is robust, efficient and gives more accurate solutions than the ones obtained with classical time-integration schemes (implicit or explicit), even when the considered meshes are coarse.